Demographic Colonialism: EU-African Migration Management and the Legacy of Eurafrica - Hansen, Peo; Jonsson, Stefan (Globalizations, 2011)
This article analyses current EU-African migration policy, but argues that it must be understood in its historical context. Whereas migration today is to be managed in the framework of an EU-African partnership model built on equality and mutual 'win-win' dynamics, a closer look at the history of EU-African migration reveals striking parallels between past and present. Throughout the period from the 1920s and onward, the migration policies devised within various frameworks of European integration have been shaped by demographic projections. Each time demography has governed European migration policy vis-à-vis Africa, what has first been introduced as a mutual interest has quickly been transformed into a geopolitical relationship, where one partner has channelled migration to its own benefit. It is thus argued that unless scholars start to attend to European integration's crucial colonial history, current power asymmetries between the 'partners' will not only remain obscure; we will also fail to recognize the continued, even increasing, currency of colonial ideology in the EU's African relations. Este artículo analiza la política de la migración entre la Unión Europea y África, pero sostiene que debe entenderse dentro del contexto histórico. Considerando que la migración hoy en día debe conducirse en el marco de un modelo de asociación entre la Unión Europea y África, con fundamento en la igualdad y las dinámicas "mutuamente beneficiosas", un análisis más detenido de la historia de la migración entre la Unión Europea y África, revela paralelos sorprendentes entre el pasado y el presente. A través del periodo que va de 1920 en adelante, las políticas de migración concebidas dentro de varios marcos de la integración europea, se han moldeado por proyecciones demográficas. Cada vez que la demografía ha regido la política de la migración europea con respecto al África, lo que se ha introducido como un interés mutuo, se ha transformado rápidamente en una relación geopolítica, en la que uno de los socios ha canalizado la migración para su propio beneficio. Por lo tanto, se plantea que a menos que los académicos comiencen a prestar atención a la historia crucial de la colonia, las asimetrías de poder entre los "socios" quedarán poco claras. También fallaremos en reconocer la vigencia continua e inclusive en aumento de la ideología colonial, en las relaciones entre la Unión Europea y África. 本文分析了当前欧盟对非洲的移民政策，认为必须在历史背景下理解这一政策。尽管当前欧盟对非洲移民问题的政策框架以平等和双赢为基础，但进一步考察移民史可发现，历史与现状有着很多相似之处。从20世纪20年代至今，每次欧洲一体化进程中的移民政策都是由人口统计学推动塑造的。人口统计学每一次都主导了欧洲的对非移民政策，因此起初以互利引入的移民政策最终都转变为地缘政治关系，其中一方依据自身利益来引导移民。因此，本文认为，除非学者关注欧洲一体化的殖民史，否则就无法认清当前"伙伴"关系间的权力不对称，也就认识不到欧盟对非关系中持续的甚至不断强化的殖民主义意识形态。